PENGARUH KOMBINASI PENGENCER SUSU SKIM DAN RINGER LAKTAT TERHADAP MOTILITAS DAN FERTILITAS SPERMATOZOA AYAM KAMPUNG (The Effect of Combination of Skim Milk and Lactated Ringer's Diluent on Motility and Fertility of Kampung Rooster Spermatozoa) - Awaludin, Khairul; Saleh, Dadang Mulyadi; Hidayat, Nu’man (JURNAL NUKLEUS PETERNAKAN, 2024)
The purpose of this study was to determine the effect of the combination of skim milk diluent and lactate ringer on the motility and fertility of kampung rooster spermatozoa. The material used was fresh chicken spermatozoa from 12 kampung rooster aged 1-1.5 years, 60 commercial laying hens at 90 weeks of age, skim milk, lactate ringer, and destilate water. This study used 2 research designs, Randomized Block Design to test motility and Completely Randomized Design to test fertility with 6 types of treatment. The treatments given were P0 = skim milk; P1=skim milk 20%+lactate ringer 80%; P2=skim milk 60%+lactate ringer 40%; P3=skim milk 40%+lactate ringer 60%; P4=skim milk 20%+lactate ringer 80%; P5 = lactate ringer. The data was analyzed using analysis of variance, then if there was a significant influence or different then a follow up test was carried out for Honest Significant Difference test was carried out. The ANOVA results showed that the combination of skim milk and Ringer's lactate diluent had a significant effect (P<0,05) on motility and no significant effect (P>0,05) on fertility. The research results showed that the highest motility value was in treatment P5= 89,75% and the lowest was in treatment P0= 82%. The highest fertility value was in treatment P0= 62,64% and the lowest was in treatment P2= 29,53%. The conclusion of this study was that Ringer lactate diluent had the highest motility value compared to other treatments, while the overall fertility value for all treatments was the same.